Studi Komparasi Model Problem-Based Learning (PBL) dan Project-Based Learning (PjBL) terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Cucini, Cucini; Suryani, Ela (Paedagogie, 2026)
The modern educational paradigm currently emphasizes various essential competencies, with creative thinking capacity being a primary element in the learning process. Nevertheless, empirical evidence in the field suggests that the development of creativity among fifth-grade students still encounters several obstacles, resulting in suboptimal outcomes. Consequently, this study was conducted to analyze and compare the effectiveness of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) models in optimizing students' creative thinking dimensions, while identifying the instructional intervention that yields the most significant impact.The methodology applied in this research is quantitative, utilizing a pre-experimental design with an intact-group comparison framework. The findings indicate that the implementation of the PjBL model produces superior outcomes compared to the PBL model. This is evidenced by the mean posttest score of the PjBL group, which reached 85.90 (categorized as excellent), whereas the PBL group attained a mean score of 80.54 (categorized as good). The disparity in these results was validated by a differential test showing a significance value of 0.003 ($< 0.05$). Based on these findings, it can be concluded that the PjBL model possesses a higher level of efficacy than PBL in accelerating the creative thinking proficiency of students.